Psychometric properties of the Telugu version of Rosenberg Self-esteem scale (RSES-T) - Billa, A. L.; Sukhabogi, J. R.; Doshi, D.; Jummala, S. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The Rosenberg Self-esteem Scale (RSES) is the most commonly used tool for measuring global self-esteem. Till date, RSES has been translated into different languages and the reports are good for their validity and reliability. Telugu being the fourth most spoken language in India, it is timely to translate and validate the Telugu version of RSES. The aim of this study thus is to assess the psychometric properties of the Telugu version of Rosenberg Self-esteem Scale (RSES-T). Study design. Cross-sectional study. Methods. This study was carried out to assess the psychometric properties of RSES-T among undergraduate students of a dental college. For this purpose, the English version of RSES was translated into Telugu and was administered to the participants along with the revised English version of Self-Liking/Self-Competence Scale (SL/SC-R) to evaluate the construct validity. The internal consistency of RSES-T was assessed using Cronbach´s α and the temporal stability was tested by test-retest reliability. Confirmatory factor analysis was conducted to examine the underlying dimensional structure of the questionnaire by assessing the correlation of RSES-T with SL/SC-R. Results. Confirmatory factor analysis revealed a positive one-factor structure with Model 3 showing the best fit to data. Internal consistency for RSES-T was found to be good with Cronbach’s α of 0.82 at follow-up and the test-retest reliability was found to be satisfactory (0.42) after a two weeks’ interval. Furthermore, the item-wise mean score differences showed higher scores for male students than females. Likewise, the item-total correlation of RSES-T showed positive correlation with scores varying from 0.17 to 0.69 at the follow-up. Conclusion. The Telugu version of RSES exhibited a unidimensional structure and showed good psychometric properties in terms of internal consistency, construct validity and reliability. Hence, these findings provide empirical support to evaluate global self-esteem among Telugu speaking population in future.